Biomechanical Behavior of Female Breast—A Review - Sheila Galbreath; Tarun Goswami (BioMed)
Introduction: Women wear exterior breast support for most of the day. A female’s breast tissue and skin affect the comfort of the ADLs, exercise, health, and work environments. Understanding the breast tissue’s normal anatomy and mechanical and material properties is related to a woman’s daily health and quality of life outcomes. Considering the importance and impact of female breasts throughout one’s lifespan, additional research is needed to address the research gaps to provide solutions to improve daily lives and clinical interventions. Breast stability and behavior are dependent on its internal mechanical properties and applied external forces. Objective: To evaluate the current knowledge and research gaps on the adult female breast tissue’s anatomy, the factors that impact its growth and development, variations among racial populations, the internal and external mechanical properties of the tissue, and the factors employed to evaluate the pathology risk. Review sections: The review sections are as follows: 3. Anatomy of Breast, 4. Effects of Age and Stages of Breast Development, 5. Breast Skin, and 6. Breast Tissue Mechanics. Conclusions: Numerous research gaps have been identified within the field of female breasts.